The Effectiveness of Team Huddles as an Interprofessional Collaboration Model in Enhancing Patient Safety Culture Within Inpatient Wards: A Systematic Literature Review - Frisa Esa Suci; Dyah Wiji Puspita Sari; Dwi Heppy Rochmawati; Muh. Abdurrouf (Jurnal Locus Penelitian dan Pengabdian, 2026)
Patient safety culture is a critical component of healthcare quality, yet interprofessional collaboration remains challenging in complex inpatient environments. Team huddles—brief, structured interprofessional meetings—have emerged as a promising intervention to enhance communication, teamwork, and safety awareness among healthcare staff. This systematic review aimed to evaluate the effectiveness of interprofessional team huddles in improving patient safety culture in inpatient wards, identify the most affected safety culture dimensions, and examine implementation barriers and facilitators. Following PRISMA guidelines, databases including SciSpace, Google Scholar, and PubMed were searched for studies published between 2010 and 2024. Eligible studies involved inpatient settings, interprofessional huddle interventions, assessment of patient safety culture using validated or qualitative methods, and reporting of implementation factors. From 248 records, 24 studies met inclusion criteria after screening. Study designs included mixed-methods, quasi-experimental, qualitative, randomized controlled trials, and reviews across diverse hospital settings. Findings indicate that huddle interventions consistently improved safety culture, particularly teamwork within units, communication openness, psychological safety, and organizational learning. Effect sizes ranged from small to moderate, with most studies reporting statistically significant improvements. Key facilitators included leadership support, structured protocols, interprofessional engagement, and protected time. Major barriers involved time constraints, hierarchical cultures, staff resistance, and limited training. Overall, interprofessional team huddles are an effective strategy for strengthening patient safety culture, though successful implementation depends on strong organizational commitment and addressing contextual barriers.